Coral Reef Conservation: Establishment of Local Communities and Introduction to Coral Lifeform in the Marine Ecotourism Area of Tobololo Beach, Ternate City - Ahmad, Aditiyawan; Susanto, Adi Noman; Irham, Irham; Aris, Muh.; Abubakar, Salim; Rumagiar, Zainul Abidin (Agrikan Jurnal Agribisnis Perikanan, 2024)
Coral reef conservation has become a topic of growing global attention, in line with the increased awareness of the importance of coral reef ecosystems for marine life and humans. The establishment of environmentally conscious local communities requires a sustainable approach. Training, education, and community empowerment programs need to be implemented to enhance understanding of the importance of coral reefs and to engage the community in conservation efforts. The issue in the ecotourism area of Tobololo Village is the lack of groups or communities that care about coral reefs, mainly because the local community does not yet understand the functions and benefits of coral reef ecosystem services. Community service activities carried out in Tobololo Village included outreach and education, the formation of a local community, and the introduction of coral reefs. The results showed that the outreach activities educated the community about coral reefs, emphasizing that they are living organisms capable of reproduction and that they have both ecological and socio-economic functions and benefits. Additionally, a local community named KOMPAG (Komunitas Masyarakat Peduli Terumbu Karang) was established.